(3GdJHjGf aj EYQGH GdbQBfs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s ((3YjSi Hf Gdgjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi habfG dMaX cJGHg s
(3GdfSNI HgG MhGTs
(3HChdgG agQS HNW eZGjQ ZjQ ebQhYI HTcd LjOs
(3HgG CKQ WeS ef CKQ GdZQbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B46s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs